2020
DOI: 10.31665/jfb.2020.10224
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-derived flavor and off-flavor of traditional and functional foods: an overview

Abstract: Flavor is an important aspect of both traditional as well as functional food acceptability and can be favorable or unfavorable depending on the chemical nature of the volatile compounds present, their potency, and the presence of non-volatile components. Lipid, as a major food component, contributes to the food flavor formation via both interactions with other components and/or due to its own degradation during food processing, cooking, and storage. This is particularly important when dealing with func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 104 publications
(114 reference statements)
0
36
0
Order By: Relevance
“…On the other hand, the phenolic compounds from plants, could be also involved in the final flavour of foods through their own taste and/or by retarding the formation of other flavour compounds, such as oxidation products [ 71 ]. It is also important to mention that thermal degradation of lipids chiefly plays a main role in Maillard reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the phenolic compounds from plants, could be also involved in the final flavour of foods through their own taste and/or by retarding the formation of other flavour compounds, such as oxidation products [ 71 ]. It is also important to mention that thermal degradation of lipids chiefly plays a main role in Maillard reaction.…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to mention that thermal degradation of lipids chiefly plays a main role in Maillard reaction. For instance, hexanal, a dominant aldehyde in meat could be produced from the oxidation of linoleic and arachidonic acids [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…For brevity, Table 5 includes the data for compounds showing concentrations higher than 4 ng equivalent of hexane/mL of headspace in any of the treatments. The aldehydes, ketones, alcohols, furans, and hydrocarbons detected are volatile compounds originating from the thermal breakdown of lipids [41][42][43]. Thus, they would have been formed mainly during the heating of the patties, and their levels would be related to the oxidative stability of lipids to heat treatment.…”
Section: Experiments 2: Headspace Volatile Composition In Cooked Pattiesmentioning
confidence: 99%
“…Changes in the lipid-derived compounds of the patty headspace resulting from ASC and BPS addition can influence patty flavour perception. The volatile compounds affected by antioxidant treatments generally have a relevant impact on cooked meat flavour [47], either directly in their original forms or as reactive intermediaries in the Maillard reaction [42]. The flavour of ASC patties may be milder, and that of BPS may be more intense.…”
Section: Experiments 2: Headspace Volatile Composition In Cooked Pattiesmentioning
confidence: 99%
“…At that moment the authors concluded that a reliance on supplements to prevent or treat COVID-19 would be premature. A cursory account of the role of lipids in flavor formation was provided by Shahidi and Oh (2020). Lipid, as a major food component, contributes to the food flavor formation via both interactions with other components and/or due to its own degradation during food processing, cooking, and storage.…”
mentioning
confidence: 99%